Do preservice teacher education candidates' implicit biases of ethnic differences and mindset toward academic ability change over time?. (April 2022) - Stephens, Jason M.; Rubie-Davies, Christine; Peterson, Elizabeth R.
Abstract: Teachers' implicit biases about ethnic differences in student achievement and teachers' mindsets have been associated with significant differences in their students' achievement. In two studies ( N  = 313; N  = 57) with preservice teachers undertaking a three-year teacher education programme aimed at promoting social justice, we found that third-year students showed significantly less implicit ethnic achievement bias and reduced fixed mindsets compared to the first-year preservice teachers. Students from the ethnic minority were found to have the least bias, but still associated student achievement more with the ethnic majority group. It is concluded that more is needed to reduce implicit biases and develop a growth mindset among our preservice teachers. Highlights: Study 1, 3rd year students demonstrated lower implicit bias than 1st year students. Study 2, students' implicit bias decreased from their 1st to 3rd year of candidacy. In both studies, fixed mindset was positively associated with implicit bias.